Glutamine synthetase in Durum Wheat: Genotypic Variation and Relationship with Grain Protein Content - Nigro, Domenica; Fortunato, Stefania; Giove, Stefania L.; Paradiso, Annalisa; Gu, Yong Q.; Blanco, Antonio; de Pinto, Maria C.; Gadaleta, Agata (Frontiers in Plant Science, 2016)
Grain protein content (GPC), is one of the most important trait in wheat and its characterized by a very complex genetic control. The identification of wheat varieties with high GPC (HGPC), as well as the characterization of central enzymes involved in these processes, are important for more sustainable agricultural practices. In this study, we focused on Glutamine synthetase (GS) as a candidate to study GPC in wheat. We analyzed GS expression and its enzymatic activity in different tissues and phenological stages in 10 durum wheat genotypes with different GPC. Although each genotype performed quite differently from the others, both because their genetic variability and their adaptability to specific environmental conditions, the highest GS activity and expression were found in genotypes with HGPC and vice versa the lowest ones in genotypes with low GPC (LGPC). Moreover, in genotypes contrasting in GPC bred at different nitrogen regimes (0, 60, 140 N Unit/ha) GS behaved differently in diverse organs. Nitrogen supplement increased GS expression and activity in roots of all genotypes, highlighting the key role of this enzyme in nitrogen assimilation and ammonium detoxification in roots. Otherwise, nitrogen treatments decreased GS expression and activity in the leaves of HGPC genotypes and did not affect GS in the leaves of LGPC genotypes. Finally, no changes in GS and soluble protein content occurred at the filling stage in the caryopses of all analyzed genotypes.